Quantification of side-effects of beta-adrenoceptor blockers using visual analogue scales. - Lewis, R V (1984)
We have devised a series of visual analogue scales (VAS) to measure the side-effects prevalent amongst hypertensive patients taking beta-adrenoceptor blockers, and we present the results of a pilot study. These show that the method is suitable for studying side-effects and suggest that patients on beta-adrenoceptor blockers experience a greater incidence of tiredness of the legs, (P = 0.001), cold digits (P = 0.005) and vivid dreaming (P = 0.01) when compared to hypertensive patients not taking beta-adrenoceptor blockers.